Analisis Efektivitas Implementasi Pendidikan Inklusif Di Sekolah - Syakirah Rahma Putri; Andara Liluyani; Adinda Rahmania Asti; Rayyana Fithras; Suhardi Suhardi (CV. ITTC INDONESIA, 2025)
In Indonesia, inclusive education still faces many complex challenges, including policy, infrastructure and human resource readiness. Many schools are not culturally and structurally ready to accept students with special needs. Limited disability-friendly facilities and infrastructure, a shortage of teachers experienced in inclusive education and a lack of community understanding of the concepts and principles of inclusion are some of the main barriers faced. Due to differences in budgets and commitment between regions, government policies to support inclusive education are not implemented evenly across regions. The aim of this study is to evaluate how effective inclusive education is and to find the components that support and hinder its success. This research used desk research, which meant reading and reviewing a wide range of relevant literature from national and international sources. These sources include scientific journals, academic books, research reports and articles that address theoretical and practical issues on inclusive education. The analysis was done descriptively to describe the current conditions and thematically to find patterns, difficulties and opportunities in implementing inclusive education. This method enables a better understanding of the social acceptance, policy development and practice of inclusive education in different contexts. The results show that there has been great progress in the area of regulation, such as the adoption of policies that support the right to education for children with special needs and increased public awareness of the importance of equal and diversity-friendly education.